1997
DOI: 10.1074/jbc.272.9.5409
|View full text |Cite
|
Sign up to set email alerts
|

The Serine/Threonine Phosphatase Inhibitor Calyculin A Induces Rapid Degradation of IκBβ

Abstract: Signal-initiated activation of the transcription factor NF-B is mediated through proteolysis of its cytoplasmic inhibitory proteins IB␣ and IB␤. While most NF-B inducers trigger the degradation of IB␣, only certain stimuli are able to induce the degradation of IB␤. The degradation of IB␣ is targeted by its sitespecific phosphorylations, although the mechanism underlying the degradation of IB␤ remains elusive. In the present study, we have analyzed the effect of phosphatase inhibitors on the proteolysis of IB␤.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
8
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 43 publications
6
8
0
Order By: Relevance
“…Data presented here provide experimental evidence to support our hypothesis. This mode of regulation for IKK is also supported by the reports that phosphatase inhibitors activate NF-B through IKK complex (5,(45)(46)(47). Furthermore, the recent crystal structure of the ␥BD of IKK␤ with IKK␥ reveals a critical intramolecular hydrogen bond within ␥BD between serine 740 and aspartate 738 (22).…”
Section: Discussionsupporting
confidence: 52%
“…Data presented here provide experimental evidence to support our hypothesis. This mode of regulation for IKK is also supported by the reports that phosphatase inhibitors activate NF-B through IKK complex (5,(45)(46)(47). Furthermore, the recent crystal structure of the ␥BD of IKK␤ with IKK␥ reveals a critical intramolecular hydrogen bond within ␥BD between serine 740 and aspartate 738 (22).…”
Section: Discussionsupporting
confidence: 52%
“…Whereas none of these mechanisms have been tested, it is tempting to speculate that a possible negative regulator may be an IKK phosphatase that is recruited to NEMO to dephosphorylate and inactivate the complex. In support of this, previous workers have demonstrated that the IKK complex can be activated by treatment with specific phosphatase inhibitors (42,43). Why then is IKK not constitutively active in NEMO Ϫ/Ϫ cells?…”
Section: Discussionmentioning
confidence: 81%
“…It is therefore of interest that calyculin A is also antiapoptotic (Song and Lavin, 1993). Clearly, this protein phosphatase inhibitor is likely to affect the phosphorylation of a wide range of additional target proteins that may have regulatory effects on apoptosis (for example, IkB; Harhaj and Sun, 1997). Nevertheless, the regulation of 4E-BP1 may contribute to the inhibition of cell death by calyculin A.…”
Section: Phosphorylation Ubiquitination and Stability Of 4e-bp1mentioning
confidence: 99%